2017
DOI: 10.1126/science.aal2490
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized, energy transfer-mediated organometallic catalysis through electronically excited nickel(II)

Abstract: Transition metal catalysis has traditionally relied on organometallic complexes that can cycle through a series of ground-state oxidation levels to achieve a series of discrete yet fundamental fragment-coupling steps. The viability of excited-state organometallic catalysis via direct photoexcitation has been demonstrated. Although the utility of triplet sensitization by energy transfer has long been known as a powerful activation mode in organic photochemistry, it is surprising to recognize that photosensitiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
430
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 434 publications
(462 citation statements)
references
References 56 publications
13
430
1
3
Order By: Relevance
“…Incorporating the photoredox cycle introduces redox or energy transfer [37] mechanisms with the nickel complexes to complete otherwise demanding catalytic cycles. Cross-coupling reactions have traditionally been catalyzed by palladium complexes at elevated temperatures to construct such critical bonds.…”
mentioning
confidence: 99%
“…Incorporating the photoredox cycle introduces redox or energy transfer [37] mechanisms with the nickel complexes to complete otherwise demanding catalytic cycles. Cross-coupling reactions have traditionally been catalyzed by palladium complexes at elevated temperatures to construct such critical bonds.…”
mentioning
confidence: 99%
“…In this context, our group has described several different transformations that employ photocatalyst excited states with nickel to enable otherwise disfavored reductive elimination steps involving C–O and C–N bonds (Figure 1). [10] Moreover, recent reports from the groups of Fu and Peters, Nocera, Molander, and Doyle describing direct photoexcitation of transition-metal catalysts provide elegant demonstrations of this paradigm. [11] Our group has also demonstrated that energy-transfer photosensitization can be used to access triplet excited states of Ni II complexes, specifically in the context of C–O bond formation between carboxylic acids and aryl halides.…”
mentioning
confidence: 99%
“…[11] Our group has also demonstrated that energy-transfer photosensitization can be used to access triplet excited states of Ni II complexes, specifically in the context of C–O bond formation between carboxylic acids and aryl halides. [10b] A key benefit of this methodology is the separation of light-harvesting and cross-coupling roles between two different transition-metal complexes. Indeed, utilization of a discrete energy-transfer catalyst bypasses the question of whether an organometallic complex can efficiently undergo direct visible-light excitation, the capacity for which often varies on a case-by-case basis.…”
mentioning
confidence: 99%
“…[141] Mit NiCl 2 und dem [Ir] 101 wurde eine Reihe von Arylbromiden 68 mit elektronenziehenden und elektronenschiebendenSubstituenten erfolgreich mit primären und sekundären Alkoholen 135 gekuppelt, was zeigt, dass die elektronische Natur der Substituenten am Arylhalogenid die Reaktivitätn icht beeinflusst (Schema 39 a). [142] Mit NiBr 2 ·Diglyme (5 Mol-%) und [Ir(ppy) 3 ] (2 Mol-%) als Photosensibilisator unter Bestrahlung mit sichtbarem Licht konnte eine Vielzahl aromatischer Verbindungen mit Alkyl-und Arylcarbonsäuren 137 gekuppelt werden, was die entsprechenden Ester 138 in guten Ausbeuten ergab.D ie Autoren schlagen vor,d ass Ir III als Sensibilisator dient, welcher sichtbares Licht absorbiert. [142] Mit NiBr 2 ·Diglyme (5 Mol-%) und [Ir(ppy) 3 ] (2 Mol-%) als Photosensibilisator unter Bestrahlung mit sichtbarem Licht konnte eine Vielzahl aromatischer Verbindungen mit Alkyl-und Arylcarbonsäuren 137 gekuppelt werden, was die entsprechenden Ester 138 in guten Ausbeuten ergab.D ie Autoren schlagen vor,d ass Ir III als Sensibilisator dient, welcher sichtbares Licht absorbiert.…”
Section: Aufsätzeunclassified